Vaccine-induced neutralizing antibodies bind to the H protein of a historical measles virus - Anne Zemella; Kerstin Beer; Franziska Ramm; Dana Wenzel; Ariane Düx; Kevin Merkel; Sebastien Calvignac-Spencer; Daniel Stern; Martin B. Dorner; Brigitte G. Dorner; Navena Widulin; Thomas Schnalke; et al. (Elsevier, 2024)
Measles is a highly contagious airborne viral disease. It can lead to serious complications and death and is preventable by vaccination. The live-attenuated measles vaccine (LAMV) derived from a measles virus (MV) isolated in 1954 has been in use globally for six decades and protects effectively by providing a durable humoral and cell-mediated immunity. Our study addresses the temporal stability of epitopes on the viral surface glycoprotein hemagglutinin (H) which is the major target of MV-neutralizing antibodies. We investigated the binding of seven vaccine-induced MV-H-specific monoclonal antibodies (mAbs) to cell-free synthesized MV-H proteins derived from the H gene sequences obtained from a lung specimen of a fatal case of measles pneumonia in 1912 and an isolate from a current case. The binding of four out of seven mAbs to the H protein of both MV strains provides evidence of epitopes that are stable for more than 100 years. The binding of the universally neutralizing mAbs RKI-MV-12b and RKI-MV-34c to the H protein of the 1912 MV suggests the long-term stability of highly conserved epitopes on the MV surface.